Surgical Treatment of Oroantral Communications. Issue 5 (July 2016) - Procacci, Pasquale; Alfonsi, Fortunato; Tonelli, Paolo; Selvaggi, Filippo; Menchini Fabris, Giovanni Battista; Borgia, Valentina; De Santis, Daniele; Bertossi, Dario; Nocini, Pier Francesco
Abstract : Background: Oroantral communication (OAC) can be defined as a pathologic space created between the maxillary sinus and the oral cavity. This communication and subsequent formation of a chronic oroantral fistula is a common complication often encountered by oral and maxillofacial surgeons. Although various techniques have been proposed in published studies, long-term successful closure of oroantral fistulas is still one of the most difficult problems confronting the surgeon working in the oral and maxillofacial region. The decision of which treatment modality to use is influenced by many factors, such as the amount and condition of tissue available for repair, the size and location of the defect, the presence of infection, the time to the diagnosis of the fistula. Objective: To evaluate an alternative technique for the treatment of oro-antral fistula, using a combined therapeutic ear nose and throat/intraoral approach. Methods: Twelve consecutive patients affected by complicated OAC were included in this study. The protocol consisted of: clinical, endoscopic, and radiological preoperative evaluation (panoramic tomogram and computed tomography); systemic antibiotic and steroid therapy for 2 weeks before surgery; one-stage surgical procedure consisting of Functional Endoscopic Sinus Surgery technique associated with the closure of the OAC by a titanium mesh and a mucoperiosteal flap; postoperative antibiotic and cortisone-based therapy. A titanium mesh was used to obtain an optimal support and stabilization of soft tissues. Follow-up consisted of weekly clinical evaluation during the first month, a clinical evaluation at 1, 3, 6, 12, 24 months and a nasal endoscopy at 3, 8, 24 weeks after surgery. A second surgical step took place to remove the mesh, after a period of healing, which went from 6 to 18 months. Samples were harvested from the surgical site after mesh removal for histological analysis. Results: At 1 month follow-up, in 10 patients of 12, the Valsalva manoeuvre was negative, same result at the 3rd month follow-up, although in 11 of 12 patients. In 5 of 12 patients, the mesh was exposed. The histological analysis confirmed the formation of a pseudo-periosteum layer. One patient failed because the mesh lost its stability. The patient was operated again 8 months later and new mesh was fixed into place. Conclusion: The current study showed that one-stage, combined endoscopic and intraoral approach represents a feasible and minimally invasive procedure for the long-term effective treatment of chronic complicated OACs. The main advantage of the use of a titanium mesh to guide the regeneration is that it assures a predictable healing, mechanic scaffold, tissues stability and allows a possible following oral rehabilitation.